The Diversity of Amphibian (Order Anura) in Bandealit Resort, Meru Betiri National Park - Siddiq, Arif Mohammad; Pradana, Yuan Zulia; Setiawan, Rendy; Sulistiyowati, Hari (BERKALA SAINSTEK, 2024)
Meru Betiri National Park (MBNP) is a conservation area located in East Java that has a diversity of flora and fauna. However, the information about entirety diversity in this area is still uncleared, due to limited scientific research, one of which is amphibians. So, the aim of this study is to explore the diversity of amphibian species (order Anura) in Bandealit Resort, MBNP. Data collection was carried out on January 6-8, 2023 in four representative habitat types i.e., terrestrial, arboreal, semi-aquatic, and aquatic. The data collection method was using Visual Encounter Surveys (VES) on each observation line with a length of 300m. The ecological data collected included the species names of amphibians (Anura) and the number of individuals of each species. Furthermore, data analysis was using species composition and species diversity using the Shannon-Wiener index (H'). Based on the results, six species of Anura were found (Fejervarya cancrivora, F. limnocharis, Leptobrachium hasseltii, Kaloula baleata, Hylarana chalconota, and Polypedates leucomystax) belonging to five families (Dicroglossidae, Megophryidae, Microhylidae, Ranidae and Rhacophoridae). Species P. leucomystax was found with the highest number of individuals (eight individuals) and occupied arboreal, terrestrial, and semi-aquatic habitat types. Based on the Shannon-Wiener index, the species diversity value of the order Anura amphibians was obtained in the moderate category (H'=1.47). This shows that the Bandealit Resort in MBNP provides an important habitat for several species of the order Anura amphibians. Furthermore, the results of this study also provide updated data regarding the existence of amphibian species of the order Anura in MBNP, especially Bandealit Resort.